2020
DOI: 10.1073/pnas.2000802117
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal mapping of bacterial membrane potential responses to extracellular electron transfer

Abstract: Extracellular electron transfer (EET) allows microorganisms to gain energy by linking intracellular reactions to external surfaces ranging from natural minerals to the electrodes of bioelectrochemical renewable energy technologies. In the past two decades, electrochemical techniques have been used to investigate EET in a wide range of microbes, with emphasis on dissimilatory metal-reducing bacteria, such as Shewanella oneidensis MR-1, as model organisms. However, due to the typically bulk nature of these techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Flavins: red, ox Figure 6: Illustration of microscopic processes in the biofilm and their dependence on pore size, surface area, and the number of cells inside the anode. A) Metabolic activity as a function of the distance to the closest anode surface (free adaption of Pirbadian et al [16]. B) Acidification in the anode as a function of distance from the bulk medium and cell density.…”
Section: P R E P R I N Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavins: red, ox Figure 6: Illustration of microscopic processes in the biofilm and their dependence on pore size, surface area, and the number of cells inside the anode. A) Metabolic activity as a function of the distance to the closest anode surface (free adaption of Pirbadian et al [16]. B) Acidification in the anode as a function of distance from the bulk medium and cell density.…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…The biofilm coverage on electrodes is not limited to single layers and can be stimulated by the presence of oxygen [Kitayama et al, 2017], possibly due to increased motility or motility elements that promote the development of three-dimensional biofilm structures [Thormann et al, 2004]. In static multilayer biofilms, electron transport from cells that are not directly attached to the electrode is facilitated by the sequential redox cycling of outer membrane c-type cytochromes and/or MET [Pirbadian et al, 2020]. In dynamic biofilms, motile cells could increase the apparent cell surface coverage [Okamoto et al, 2012], enabling more cells to participate in EET.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found current generation from S. oneidensis can vary, from ∼2 fA • cell −1 in cell suspensions to soluble riboflavin, to ∼100-200 fA • cell −1 in single cells to electrodes (18, 23, 49). Methods measuring larger reduction rates have varied in experimental conditions, including extrapolating single cell EET from biofilms on electrodes or hematite nanoparticles (14, 1819, 4950). One primary difference in our study compared to these is the lack of cell immobilization on a surface.…”
Section: Resultsmentioning
confidence: 99%
“…One primary difference in our study compared to these is the lack of cell immobilization on a surface. Cell motility may inhibit certain EET mechanisms such as flavin shuttling, which occurs primarily in attached cytochromes (19, 51). Therefore, it is possible that both physiological and experimental differences account for increased EET measurement in these platforms compared to ours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation